A mouse model of early-onset renal failure due to a xanthine dehydrogenase nonsense mutation. - Piret, S; Esapa, C; Gorvin, C; Head, R; Loh, N; Devuyst, O; Thomas, G; Brown, s; Brown, M; Croucher, P; Cox, R; Thakker, R (Public Library of Science, 2012)
Chronic kidney disease (CKD) is characterized by renal fibrosis that can lead to end-stage renal failure, and studies have supported a strong genetic influence on the risk of developing CKD. However, investigations of the underlying molecular mechanisms are hampered by the lack of suitable hereditary models in animals. We therefore sought to establish hereditary mouse models for CKD and renal fibrosis by investigating mice treated with the chemical mutagen N-ethyl-N-nitrosourea, and identified a mouse with autosomal recessive renal failure, designated RENF. Three-week old RENF mice were smaller than their littermates, whereas at birth they had been of similar size. RENF mice, at 4-weeks of age, had elevated concentrations of plasma urea and creatinine, indicating renal failure, which was associated with small and irregularly shaped kidneys. Genetic studies using DNA from 10 affected mice and 91 single nucleotide polymorphisms mapped the Renf locus to a 5.8 Mbp region on chromosome 17E1.3. DNA sequencing of the xanthine dehydrogenase (Xdh) gene revealed a nonsense mutation at codon 26 that co-segregated with affected RENF mice. The Xdh mutation resulted in loss of hepatic XDH and renal Cyclooxygenase-2 (COX-2) expression. XDH mutations in man cause xanthinuria with undetectable plasma uric acid levels and three RENF mice had plasma uric acid levels below the limit of detection. Histological analysis of RENF kidney sections revealed abnormal arrangement of glomeruli, intratubular casts, cellular infiltration in the interstitial space, and interstitial fibrosis. TUNEL analysis of RENF kidney sections showed extensive apoptosis predominantly affecting the tubules. Thus, we have established a mouse model for autosomal recessive early-onset renal failure due to a nonsense mutation in Xdh that is a model for xanthinuria in man. This mouse model could help to increase our understanding of the molecular mechanisms associated with renal fibrosis and the specific roles of XDH and uric acid.